Composition and spatio-temporal variation of the fish community in the Chacmochuch Lagoon system, Quintana Roo, Mexico - Caballero-Vázquez, J. Adán; Gamboa-Pérez, Héctor C.; Schmitter-Soto, Juan J. (HIDROBIOLÓGICA, 2017)
The composition, distribution and abundance of fishes were determined in the Chacmochuch Lagoon System, a natural protected area located on the north coast of Quintana Roo. Monthly diurnal sampling was carried out at 10 sampling stations in March, June and September, 2002. During each field trip, bottom type, submerged and surrounding vegetation, salinity, temperature, dissolved oxygen and other variables were measured. Distribution and abundance of fishes were examined by means of a principal component analysis. Fifty species were recorded; Gerres cinereus, Floridichthys polyommus, Eugerres plumieri, Harengula jaguana, Sphyraena barracuda, and Archosargus rhomboidalis were dominant, and no significant difference in species composition was found between seasons. Apart from a single site where turbidity and nutrient concentration were particularly high, the other sites could be classified mainly according to salinity. Fish composition changed along this gradient.